2012
DOI: 10.1152/ajpheart.00464.2012
|View full text |Cite
|
Sign up to set email alerts
|

PACAP causes PAC1/VPAC2 receptor mediated hypertension and sympathoexcitation in normal and hypertensive rats

Abstract: Farnham MM, Lung MS, Tallapragada VJ, Pilowsky PM. PACAP causes PAC 1/VPAC2 receptor mediated hypertension and sympathoexcitation in normal and hypertensive rats. Am J Physiol Heart Circ Physiol 303: H910 -H917, 2012. First published August 10, 2012; doi:10.1152/ajpheart.00464.2012.-Pituitary adenylate cyclase-activating polypeptide (PACAP) is an excitatory neuropeptide that plays an important role in hypertension and stress responses. PACAP acts at three G protein-coupled receptors [PACAP type 1 receptor (PAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 67 publications
1
34
1
Order By: Relevance
“…This is in keeping with our finding that the G as subunit mRNA is abundant in the RVLM (Parker et al, 2012) and consistent with a postsynaptic site of action, as suggested previously in neonatal RVLM brain slice preparations, in which 8-Br-cAMP and the adenylyl cyclase activator forskolin increased the firing rate of RVLM "pacemaker" neurons in the presence of tetrodotoxin (Sun and Guyenet, 1990). Activation of G as -linked receptors in the RVLM using pituitary adenylate cyclase-activating peptide evokes sympathoexcitation and pressor responses, although reflex functions were unaffected (Farnham et al, 2012). On cAMP Signaling in the Ventrolateral Medulla the other hand, cardiac vagal nerve activity is increased by systemic adenosine (da Silva et al, 2012) or by activation of b-adrenergic receptors, specifically b1, which reduces GABAergic and glycinergic (as well as glutamatergic) conductances at cardiac vagal preganglionic neurons (Bateman et al, 2012).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This is in keeping with our finding that the G as subunit mRNA is abundant in the RVLM (Parker et al, 2012) and consistent with a postsynaptic site of action, as suggested previously in neonatal RVLM brain slice preparations, in which 8-Br-cAMP and the adenylyl cyclase activator forskolin increased the firing rate of RVLM "pacemaker" neurons in the presence of tetrodotoxin (Sun and Guyenet, 1990). Activation of G as -linked receptors in the RVLM using pituitary adenylate cyclase-activating peptide evokes sympathoexcitation and pressor responses, although reflex functions were unaffected (Farnham et al, 2012). On cAMP Signaling in the Ventrolateral Medulla the other hand, cardiac vagal nerve activity is increased by systemic adenosine (da Silva et al, 2012) or by activation of b-adrenergic receptors, specifically b1, which reduces GABAergic and glycinergic (as well as glutamatergic) conductances at cardiac vagal preganglionic neurons (Bateman et al, 2012).…”
Section: Discussionsupporting
confidence: 86%
“…It is possible that blocking PKA may redistribute the active pool of cAMP to other effectors; however, at least in the RVLM, blocking either EPAC or HCN channels alone had little effect. There is little evidence supporting the idea of tonically active peptides in the RVLM Pilowsky et al, 2008;Farnham et al, 2012). Nevertheless the findings here suggest that a neurotransmitter acting via G aslinked receptor/s is active in the ventrolateral medulla.…”
Section: Discussioncontrasting
confidence: 74%
“…Glutamate is a major excitatory neurotransmitter, and responsible for normal maintenance of reflex responses (Miyawaki et al, 1996;Pilowsky and Goodchild, 2002;Pilowsky et al, 2009), which also plays an important role in the development of seizure (Casillas-Espinosa et al, 2012;Powell et al, 2014a;Bhandare et al, 2016b). Heart-rate baroreflex sensitivity decreases with intracerebroventricular injection of PACAP in trout (Lancien et al, 2011), whereas in rats, PACAP agonist or antagonist microinjection into the RVLM produce no significant effect (Farnham et al, 2012). In spontaneously hypertensive rats, increased microglial activation, and pro-inflammatory cytokines in PVN causes autonomic (baroreflex) dysfunction (Masson et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…During acute seizures, PACAP and microglia act on presympathetic rostral ventrolateral medulla (RVLM) neurons in the brainstem to promote proarrhythmogenic changes, but not sympathoexcitation . In many cardiovascular autonomic nuclei PACAP is pressor and sympathoexcitatory (Farnham et al, 2008;Farnham et al, 2011;Inglott et al, 2011) and changes baroreflex response in trout (Lancien et al, 2011) but not in rats (Farnham et al, 2012). PACAP expression is increased in central autonomic nuclei (paraventricular nucleus) after kainic acid (KA)-induced seizures in rats (Nomura et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, PACAP-38 causes hyperthermia in rats [16,17], counteracts reserpine-induced hypothermia [6], depresses the intake of food [18] and water intake [19], inhibits open-field activity [20]. PACAP plays an important role in hypertension and stress response [21].…”
Section: Introductionmentioning
confidence: 99%